Nematode parasites of the Chilean Flamingo, Phoenicopterus chilensis (Phoenicopteridae) from Central Argentina, with a description of a new species of Tetrameres (Tetrameridae) - Núñez, María Verónica (2017)
During the summer of 2013, several specimens of Phoenicopterus chilensis (Phoenicopteridae) were found dead from unknown causes, in lakes from the endorheic system "Encadenadas del Oeste", Buenos Aires Province, Argentina. Two species of Nematoda were recovered from the proventriculus, one of them new for science. The tetramerid Tetrameres (Tetrameres) salina n. sp. is mainly characterized by having reduced pseudolabia, lips absent, six bifid teeth, males with lateral alae, four rows of somatic spines and length ratio of spicules 1:12–32, and large females with eggs lacking polar filaments. The acuariid, Echinuria skrjabinensis is described and illustrated, this finding represent the second report of this nematode in Argentina and the first record in flamingos. This is the first record of helminths parasitizing wild Chilean Flamingos, but it is not possible to ensure that they accomplish their life cycle in this system of lakes, because the migratory movements of the population of flamingos studied are unknown.